QM/MM dynamics of Proton Transport in Chitosan/Phosphotungstic Acid Composite Membrane for Direct Methanol Fuel Cell - Sundarti, Linda Windia (IPTEK Journal of Proceedings Series, 2015)
The aim of this research is to study proton transport in DMFC using chitosan/phosphotungstic acid (CS/PWA) composite membrane as Proton Exchange Membrane (PEM). Model of proton transport mechanism was proposed in order to investigate the proton transport rationality in CSPWA composite membrane, which is indicated by energy models. QM/MM dynamics method on the basis of CP2K code was used to calculate energy of the models. Results showed that the model of proton transport mechanism produced energy gradient. Interaction model of proton (H+ ion) and CS/PWA hydrated membrane has minimum QM/MM energy than the other models. The value of QM/MM energy of H+-CS/PWA hydrated is -312.717135970308 a.u